Mud cake hardening enhancer for drilling fluid and preparation method of mud cake hardening enhancer
By using raw materials and treatment methods with specific ratios, mud cake hardening enhancers for drilling fluids are prepared, forming a porous active structure and a light crosslinking network, the problem of easy degradation of mud cake hardening enhancers in the prior art is solved, and the cementing strength and viscosity performance of the drilling fluid are significantly improved.
Patent Information
- Application Number
- CN202510400680.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-01
AI Technical Summary
The existing mud cake hardening enhancer for drilling fluids is prone to degradation in the underground operating environment, resulting in a decrease in cementation strength and affecting the performance of drilling fluids.
The mud cake hardening enhancer for drilling fluid is prepared by using bishydroxyethoxypropyl polydimethylsiloxane, hardening agent, modified starch, film forming agent, additive, chelating agent and asbestos, through specific mixing and treatment methods, forming a porous active structure and a light crosslinking network to improve the cementing strength and viscosity performance of mud cake.
It effectively improves the cementing strength and viscosity performance of the drilling fluid, enhances the compressive resistance of the mud cake, reduces the risk of well wall collapse, reduces the brittleness of the mud cake, and improves the efficiency of the drilling fluid.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling, in particular to a mud cake hardening enhancer for drilling fluid and a preparation method thereof. Background Art
[0002] Mud cake hardening enhancer for drilling fluid is an additive used in drilling fluid, which can improve the bonding and viscosity properties of drilling fluid, enhance the strength and stability of mud cake, and ensure the smooth progress of drilling operations.
[0003] In the prior art, the conventional mud cake hardening enhancer for drilling fluid is made of a single polymer, which has a single molecular chain structure and is easily degraded in the underground working environment, resulting in a significant decrease in the bonding strength, which affects the performance of the drilling fluid. Based on this, the present invention provides a mud cake hardening enhancer for drilling fluid and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a mud cake hardening enhancer for drilling fluid and a preparation method thereof. The mud cake hardening enhancer for drilling fluid prepared by the present invention not only has good bonding strength performance, but also has excellent viscosity performance, which effectively improves the use performance of drilling.
[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a mud cake hardening enhancer for drilling fluid, comprising the following raw materials in parts by weight: 60 to 80 parts of bishydroxyethoxypropyl polydimethylsiloxane, 40 to 60 parts of a hardener, 10 to 20 parts of modified starch, 6 to 8 parts of a film-forming agent, 4 to 6 parts of an additive, 4 to 6 parts of a chelating agent and 2 to 4 parts of asbestos.
[0006] Furthermore, the additive is prepared by the following method: acrylic acid and pure water are mixed in a beaker, the mass ratio of acrylic acid to pure water is 1:(0.2-0.3), sodium hydroxide solution is added dropwise after sufficient mixing, the mass of the sodium hydroxide solution is 1.2-1.3 times the mass of acrylic acid, and the mass concentration of the sodium hydroxide solution is 30-40%, and after the addition is completed, the mixture is fully mixed, heated in a water bath to 40-50°C, and kept warm for 6-10 minutes to obtain a first mixture.
[0007] Furthermore, a sodium sulfite solution is added to the first mixture, the mass of the sodium sulfite solution is 0.4-0.8% of the mass of the mixed liquid, and the mass concentration of the sodium sulfite solution is 18-20%. After mixing, the mixture is heated in a water bath to 50-54° C. and kept warm for 10-14 minutes to obtain a second mixture. After mixing, the second mixture is sent to an ultraviolet curing agent at a distance of 20-30 cm from the light source and cured for 1-3 hours to obtain an additive.
[0008] Furthermore, the hardener is prepared by the following method: the hardener selects rice husk as a base material, the rice husk is cleaned and dried, and then ground into powder with a particle size of 20 to 30 μm to obtain a first powder.
[0009] Furthermore, the first powder is mixed with sulfuric acid in a beaker, the mass of the sulfuric acid is 8 to 12 times the mass of the first powder, and the concentration of the sulfuric acid is 5 to 7%. After mixing, the mixture is heated in a water bath to 50 to 60°C, and a magnetic stirrer is set to stir at 160 to 200 r / min. The mixture is kept warm and stirred for 10 to 20 minutes, and then filtered to obtain a solution. The solution is repeated with the above steps 2 to 4 times, and the product is dried to obtain a slag. The slag is ground to a powder particle size of 6 to 10 μm. The ground slag is fed into a carbonization furnace, and the carbonization furnace is set to a heating rate of 10 to 12°C / min, and the temperature is raised to 450 to 550°C, and the temperature is kept warm for 20 to 30 minutes. Nitrogen is introduced during the heating process to obtain a hardener.
[0010] Furthermore, the modified starch is prepared by the following method: the modified starch uses chickpea as a base material, the chickpea is washed, dried, and ground into powder, the particle size of the powder is 10 to 20 μm, and the second powder is prepared.
[0011] Furthermore, the second powder is mixed with deionized water and added to a reactor, the mass ratio of the second powder to deionized water is 1:(4-6), the reactor is set at 200-300 r / min and stirred for 10-20 min, sodium bicarbonate is added to the obtained product to adjust the pH value to 7-8, octenyl succinic anhydride is added to the reactor, the mass of the octenyl succinic anhydride is 2-4% of the mass of the second powder, the reactor is set to heat up to 40-50°C, the speed is 80-100 r / min, and the heat preservation and stirring are carried out for 4-6 min. The product obtained by the heat preservation and stirring treatment is added to a centrifuge for centrifugal treatment, the centrifuge is set at 4000-5000 r / min for 6-10 min, the supernatant is discarded, and a precipitate is obtained. The obtained precipitate is sent to an oven, the oven is set at 42-44°C for drying for 50-60 min, and then ground, the grinding particle size is 6-10 μm, and modified starch is obtained.
[0012] Furthermore, the film-forming agent is polymethyl methacrylate.
[0013] Furthermore, the chelating agent is ethylethylenediaminetriacetic acid, and the asbestos is selected to have a fiber length of 20 to 40 μm and a diameter of 0.4 to 1 μm.
[0014] In a second aspect, the present invention further provides a method for preparing a mud cake hardening enhancer for drilling fluid, comprising the following steps: S1: Weigh bishydroxyethoxypropyl polydimethylsiloxane, film-forming agent, chelating agent and asbestos as needed and add them into a mixer. Set the mixer to 800-1000 r / min and stir for 1-3 hours to obtain a primary mixture; S2: adding a hardener, an additive and modified starch to the primary mixture, setting the mixer at 200-400 r / min for stirring for 6-8 minutes, and preparing a mud cake hardening enhancer for drilling fluid.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, by adding a hardener during the preparation process of the mud cake hardening enhancer for drilling fluid, the hardener is treated with rice husk as the base material, and the rice husk is acid-lyzed and carbonized to form a porous active structure, which is adsorbed and tightly bonded with the modified starch material in the mud cake hardening enhancer for drilling fluid, thereby improving the bonding strength between the mud cake and the well wall. A lightly cross-linked network is formed in the hardener obtained by ultraviolet light treatment, which can give the mud cake a skeleton support structure. The cross-linked network enhances the compressive strength of the mud cake through intermolecular entanglement, reduces the risk of well wall collapse, reduces the brittleness of the mud cake, avoids cracking caused by downhole pressure fluctuations, and effectively improves the use efficiency of the drilling fluid.
[0016] 2. In the present invention, modified starch is added in the preparation process of the mud cake hardening enhancer for drilling fluid. The modified starch made with chickpea as the base material has abundant hydrophilic groups. The hydrophilic groups can form hydrogen bond interactions with water molecules, so that the modified starch has good hydrophilicity. After being added to the drilling fluid, the modified starch absorbs water to form a viscous network. With the addition of asbestos, the well wall interface bonding force of the mud cake is effectively improved, thereby increasing the internal friction of the drilling fluid and improving the viscosity performance of the drilling fluid. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] It should be noted that the raw materials used in the following examples are all commercially available raw materials.
[0019] Embodiment 1
[0020] The invention comprises the following raw materials in parts by weight: 60 parts of bishydroxyethoxypropyl polydimethylsiloxane, 40 parts of hardener, 10 parts of modified starch, 6 parts of film former, 4 parts of additive, 4 parts of chelating agent and 2 parts of asbestos.
[0021] The additive is prepared by the following method: acrylic acid and pure water are mixed in a beaker, the mass ratio of acrylic acid to pure water is 1: (0.2), sodium hydroxide solution is added dropwise after fully mixing, the mass of the sodium hydroxide solution is 1.2 times the mass of acrylic acid, and the mass concentration of the sodium hydroxide solution is 30%, after the addition is completed, the mixture is fully mixed, heated to 40° C. in a water bath, and kept warm for 6 minutes to obtain a first mixture.
[0022] Sodium sulfite solution was added to the first mixture, the mass of the sodium sulfite solution was 0.4% of the mass of the mixed liquid, and the mass concentration of the sodium sulfite solution was 18%. After mixing, the mixture was heated to 50°C in a water bath and kept warm for 10 minutes to obtain a second mixture. After mixing, the second mixture was sent into an ultraviolet curing agent at a distance of 20 cm from the light source and cured for 1 hour to obtain an additive.
[0023] The hardener is prepared by the following method: the hardener selects rice husk as a base material, washes and dries the rice husk, and then grinds it into powder with a particle size of 20 μm to prepare a first powder.
[0024] The first powder and sulfuric acid are mixed in a beaker, the mass of the sulfuric acid is 8 times the mass of the first powder, and the concentration of the sulfuric acid is 5%. After mixing, the mixture is heated to 50°C in a water bath, and stirred at 160r / min using a magnetic stirrer. The mixture is kept warm and stirred for 10 minutes, and then filtered to obtain a solution. The solution is repeated with the above steps twice, and the product is dried to obtain a slag. The slag is ground to a powder particle size of 6μm. The ground slag is fed into a carbonization furnace, and the carbonization furnace is set to a heating rate of 10°C / min, and the temperature is raised to 450°C, and the temperature is kept warm for 20 minutes. Nitrogen is introduced during the heating process to obtain a hardener.
[0025] The modified starch is prepared by the following method: chickpea is selected as the base material of the modified starch, the chickpea is washed, dried and ground into powder with a particle size of 10 μm to prepare the second powder.
[0026] The second powder is mixed with deionized water and added to a reactor, wherein the mass ratio of the second powder to deionized water is 1:(4). The reactor is set to stir at 200 r / min for 10 min, and sodium bicarbonate is added to the obtained product to adjust the pH value to 7. Octenyl succinic anhydride is added to the reactor, and the mass of octenyl succinic anhydride is 2% of the mass of the second powder. The reactor is set to heat to 40°C and rotate at 80 r / min. The mixture is stirred at this temperature for 4 min. The product obtained by stirring and keeping warm is added to a centrifuge for centrifugal treatment. The centrifuge is set at 4000 r / min for 6 min. The supernatant is discarded to obtain a precipitate. The obtained precipitate is sent to an oven, which is set at 42°C for drying for 50 min, and then ground to obtain a powder with a particle size of 6 μm. Modified starch is obtained.
[0027] The film-forming agent is polymethyl methacrylate.
[0028] The chelating agent is ethylethylenediaminetriacetic acid, and the asbestos is selected with a fiber length of 20 μm and a diameter of 0.4 μm.
[0029] A method for preparing a mud cake hardening enhancer for drilling fluid comprises the following steps: S1: Weigh bishydroxyethoxypropyl polydimethylsiloxane, film-forming agent, chelating agent and asbestos as needed and add them into a mixer. Set the mixer to 800 r / min and stir for 1 hour to obtain a primary mixture; S2: Add hardener, additives and modified starch to the primary mixture, set the mixer at 200 r / min and stir for 6 minutes to obtain a mud cake hardening enhancer for drilling fluid.
[0030] Embodiment 2
[0031] The invention comprises the following raw materials in parts by weight: 70 parts of bishydroxyethoxypropyl polydimethylsiloxane, 50 parts of hardener, 15 parts of modified starch, 7 parts of film former, 5 parts of additive, 5 parts of chelating agent and 3 parts of asbestos.
[0032] The additive is prepared by the following method: acrylic acid and pure water are mixed in a beaker, the mass ratio of acrylic acid to pure water is 1: (0.25), sodium hydroxide solution is added dropwise after thorough mixing, the mass of the sodium hydroxide solution is 1.25 times the mass of acrylic acid, and the mass concentration of the sodium hydroxide solution is 35%, after the addition is completed, the mixture is thoroughly mixed, heated to 45° C. in a water bath, and kept warm for 8 minutes to obtain a first mixture.
[0033] Sodium sulfite solution was added to the first mixture, the mass of the sodium sulfite solution was 0.6% of the mass of the mixed liquid, and the mass concentration of the sodium sulfite solution was 19%. After mixing, it was heated to 52° C. in a water bath and kept warm for 12 minutes to obtain a second mixture. After mixing, the second mixture was sent into an ultraviolet curing agent at a distance of 25 cm from the light source and cured for 2 hours to obtain an additive.
[0034] The hardener is prepared by the following method: the hardener selects rice husk as the base material, the rice husk is cleaned and dried, and then ground into powder with a particle size of 25 μm to obtain the first powder.
[0035] The first powder and sulfuric acid are mixed in a beaker, the mass of the sulfuric acid is 10 times the mass of the first powder, and the concentration of the sulfuric acid is 6%. After mixing, the mixture is heated to 55°C in a water bath, and stirred at 180r / min using a magnetic stirrer. The mixture is kept warm and stirred for 15 minutes, and then filtered to obtain a solution. The solution is repeated with the above steps for 3 times, and the obtained product is dried to obtain a slag. The slag is ground to a powder particle size of 8μm. The ground slag is fed into a carbonization furnace, and the carbonization furnace is set to a heating rate of 11°C / min, and the temperature is raised to 500°C, and the temperature is kept warm for 25 minutes. Nitrogen is introduced during the heating process to obtain a hardener.
[0036] The modified starch is prepared by the following method: chickpea is selected as the base material of the modified starch, the chickpea is washed, dried and ground into powder with a particle size of 15 μm to prepare the second powder.
[0037] The second powder was mixed with deionized water and added to a reactor, wherein the mass ratio of the second powder to deionized water was 1:(5). The reactor was set at 250 r / min and stirred for 15 min. Sodium bicarbonate was added to the obtained product to adjust the pH value to 7.5. Octenyl succinic anhydride was added to the reactor, wherein the mass of the octenyl succinic anhydride was 3% of the mass of the second powder. The reactor was set to heat to 45°C and rotate at 90 r / min. The mixture was stirred for 5 min at this temperature. The product obtained by the stirring and keeping temperature was added to a centrifuge for centrifugal treatment. The centrifuge was set at 4500 r / min for 8 min. The supernatant was discarded to obtain a precipitate. The obtained precipitate was sent to an oven, which was set at 43°C for drying for 55 min. The precipitate was then ground to a particle size of 8 μm to obtain modified starch.
[0038] The film-forming agent is polymethyl methacrylate.
[0039] The chelating agent selected is ethylethylenediaminetriacetic acid, and the asbestos selected is a fiber with a length of 30 μm and a diameter of 0.7 μm.
[0040] A method for preparing a mud cake hardening enhancer for drilling fluid comprises the following steps: S1: Weigh bishydroxyethoxypropyl polydimethylsiloxane, film-forming agent, chelating agent and asbestos as needed and add them into a mixer. Set the mixer to 900 r / min and stir for 2 h to obtain a primary mixture; S2: Add hardener, additives and modified starch to the primary mixture, set the mixer at 300 r / min and stir for 7 minutes to obtain a mud cake hardening enhancer for drilling fluid.
[0041] Embodiment 3
[0042] The invention comprises the following raw materials in parts by weight: 80 parts of bishydroxyethoxypropyl polydimethylsiloxane, 60 parts of hardener, 20 parts of modified starch, 8 parts of film former, 6 parts of additive, 6 parts of chelating agent and 4 parts of asbestos.
[0043] The additive is prepared by the following method: acrylic acid and pure water are mixed in a beaker, the mass ratio of acrylic acid to pure water is 1: (0.3), sodium hydroxide solution is added dropwise after thorough mixing, the mass of the sodium hydroxide solution is 1.3 times the mass of acrylic acid, and the mass concentration of the sodium hydroxide solution is 40%, after the addition is completed, the mixture is thoroughly mixed, heated to 50° C. in a water bath, and kept warm for 10 minutes to obtain a first mixture.
[0044] Sodium sulfite solution was added to the first mixture, the mass of the sodium sulfite solution was 0.8% of the mass of the mixed liquid, and the mass concentration of the sodium sulfite solution was 20%. After mixing, the mixture was heated to 54°C in a water bath and kept warm for 14 minutes to obtain a second mixture. After mixing, the second mixture was sent into an ultraviolet curing agent at a distance of 30 cm from the light source and cured for 3 hours to obtain an additive.
[0045] The hardener is prepared by the following method: the hardener selects rice husk as the base material, washes and dries the rice husk, and then grinds it into powder with a particle size of 30 μm to prepare the first powder.
[0046] The first powder and sulfuric acid are mixed in a beaker, the mass of the sulfuric acid is 12 times the mass of the first powder, and the concentration of the sulfuric acid is 7%. After mixing, the mixture is heated to 60°C in a water bath, and stirred at 200r / min using a magnetic stirrer. The mixture is kept warm and stirred for 20 minutes, and then filtered to obtain a solution. The solution is repeated with the above steps 4 times, and the obtained product is dried to obtain a slag. The slag is ground to a powder particle size of 10μm. The ground slag is fed into a carbonization furnace, and the carbonization furnace is set to a heating rate of 12°C / min, and the temperature is raised to 550°C, and the temperature is kept warm for 30 minutes. Nitrogen is introduced during the heating process to obtain a hardener.
[0047] The modified starch is prepared by the following method: chickpeas are selected as the base material of the modified starch, the chickpeas are washed, dried, and ground into powder with a particle size of 20 μm to prepare the second powder.
[0048] The second powder is mixed with deionized water and added to a reactor, wherein the mass ratio of the second powder to deionized water is 1:(6). The reactor is set at 300 r / min and stirred for 20 min. Sodium bicarbonate is added to the obtained product to adjust the pH value to 8. Octenyl succinic anhydride is added to the reactor, wherein the mass of octenyl succinic anhydride is 4% of the mass of the second powder. The reactor is set to heat up to 50°C and rotate at 100 r / min. The mixture is stirred for 6 min. The product obtained by the stirring and keeping warm is added to a centrifuge for centrifugal treatment. The centrifuge is set at 5000 r / min for 10 min. The supernatant is discarded to obtain a precipitate. The obtained precipitate is sent to an oven, which is set at 44°C for drying for 60 min. The precipitate is then ground to a particle size of 10 μm to obtain modified starch.
[0049] The film-forming agent is polymethyl methacrylate.
[0050] The chelating agent is ethylethylenediaminetriacetic acid, and the asbestos is selected with a fiber length of 40 μm and a diameter of 1 μm.
[0051] A method for preparing a mud cake hardening enhancer for drilling fluid comprises the following steps: S1: Weigh bishydroxyethoxypropyl polydimethylsiloxane, film-forming agent, chelating agent and asbestos as needed and add them into a mixer. Set the mixer to 1000 r / min and stir for 3 hours to obtain a primary mixture. S2: Add hardener, additives and modified starch to the primary mixture, set the mixer at 400 r / min and stir for 8 minutes to obtain a mud cake hardening enhancer for drilling fluid.
[0052] Comparative Example 1: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of corn starch is used to replace the hardener.
[0053] Comparative Example 2: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of corn starch is used to replace the modified starch.
[0054] Comparative Example 3: The difference between this comparative example and Example 1 is that no modified starch is added in this comparative example.
[0055] Comparative Example 4: The difference between this comparative example and Example 1 is that no hardener is added in this comparative example.
[0056] Performance test: The performance test was performed on the mud cake hardening enhancers for drilling fluid prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and the obtained test data are recorded in the following table:
[0057] In the performance test, at 130° C., the mud cake hardening enhancer for drilling fluid prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 was added to the drilling fluid in an amount of 3%, and various properties of the drilling fluid were tested.
[0058] It can be seen that the bonding strength and viscosity performance of the mud cake hardening enhancer for drilling fluid prepared in Comparative Examples 1, 2, 3 and 4 are lower than those in Examples 1, 2 and 3; this shows that: by adding the hardener in the preparation process of the mud cake hardening enhancer for drilling fluid, the hardener is treated with rice husk as the base material, and the rice husk is acid-lyzed and carbonized to form a porous active structure, which is tightly adsorbed and bonded with the modified starch material in the mud cake hardening enhancer for drilling fluid, thereby improving the bonding strength between the mud cake and the well wall, and a slightly cross-linked network is formed in the hardener obtained by ultraviolet light treatment, which can give the mud cake a skeleton support structure, and the cross-linked network can enhance the strength of the mud cake by intermolecular entanglement. The mud cake compressive resistance reduces the risk of well wall collapse, reduces the brittleness of the mud cake, avoids cracking caused by downhole pressure fluctuations, and effectively improves the use efficiency of the drilling fluid. By adding modified starch in the preparation process of the mud cake hardening enhancer for drilling fluid, the modified starch made with chickpea as the base material has rich hydrophilic groups. The hydrophilic groups can form hydrogen bonds with water molecules, making the modified starch have good hydrophilicity. After being added to the drilling fluid, the modified starch absorbs water to form a viscous network. With the addition of asbestos, the well wall interface bonding of the mud cake is effectively improved, thereby increasing the internal friction of the drilling fluid and improving the viscosity performance of the drilling fluid.
[0059] By comparing and analyzing the relevant data in the table, it can be seen that the mud cake hardening enhancer for drilling fluid prepared by the present invention not only has good bonding strength performance, but also has excellent viscosity performance. This shows that the mud cake hardening enhancer for drilling fluid provided by the present invention has a broader market prospect and is more suitable for promotion.
[0060] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0061] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A mud cake hardening enhancer for drilling fluid, characterized in that: The invention comprises the following raw materials in parts by weight: 60 to 80 parts of bishydroxyethoxypropyl polydimethylsiloxane, 40 to 60 parts of hardener, 10 to 20 parts of modified starch, 6 to 8 parts of film former, 4 to 6 parts of additive, 4 to 6 parts of chelating agent and 2 to 4 parts of asbestos.
2. The mud cake hardening enhancer for drilling fluid according to claim 1, characterized in that: The additive is prepared by the following method: acrylic acid and pure water are mixed in a beaker, the mass ratio of acrylic acid to pure water is 1:(0.2-0.3), sodium hydroxide solution is added dropwise after fully mixing, the mass of the sodium hydroxide solution is 1.2-1.3 times the mass of acrylic acid, and the mass concentration of the sodium hydroxide solution is 30-40%, after the dropwise addition is completed, the mixture is fully mixed, heated in a water bath to 40-50° C., and kept warm for 6-10 minutes to obtain a first mixed material.
3. The mud cake hardening enhancer for drilling fluid according to claim 2, characterized in that: A sodium sulfite solution is added to the first mixed material, wherein the mass of the sodium sulfite solution is 0.4-0.8% of the mass of the mixed liquid, and the mass concentration of the sodium sulfite solution is 18-20%. After mixing, the mixture is heated in a water bath to 50-54° C. and kept warm for 10-14 minutes to obtain a second mixed material. After mixing, the second mixed material is sent into an ultraviolet curing agent at a distance of 20-30 cm from the light source and cured for 1-3 hours to obtain an additive.
4. The mud cake hardening enhancer for drilling fluid according to claim 1, characterized in that: The hardener is prepared by the following method: the hardener selects rice husk as a base material, washes and dries the rice husk, and then grinds it into powder with a particle size of 20 to 30 μm to prepare a first powder.
5. The mud cake hardening enhancer for drilling fluid according to claim 4, characterized in that: The first powder and sulfuric acid are mixed in a beaker, the mass of the sulfuric acid is 8 to 12 times the mass of the first powder, and the concentration of the sulfuric acid is 5 to 7%. After mixing, the mixture is heated in a water bath to 50 to 60°C, and a magnetic stirrer is used to stir at 160 to 200 r / min. The mixture is kept warm and stirred for 10 to 20 minutes, and then filtered to obtain a solution. The solution is repeated with the above steps 2 to 4 times, and the product is dried to obtain a slag. The slag is ground to a powder particle size of 6 to 10 μm. The ground slag is fed into a carbonization furnace, and the carbonization furnace is set to a heating rate of 10 to 12°C / min, and the temperature is raised to 450 to 550°C, and the temperature is kept warm for 20 to 30 minutes. Nitrogen is introduced during the heating process to obtain a hardener.
6. The mud cake hardening enhancer for drilling fluid according to claim 1, characterized in that: The modified starch is prepared by the following method: chickpea is selected as the base material of the modified starch, the chickpea is washed, dried and ground into powder, the particle size of the ground powder is 10-20 μm, and the second powder is prepared.
7. The mud cake hardening enhancer for drilling fluid according to claim 6, characterized in that: The second powder is mixed with deionized water and added into a reactor, wherein the mass ratio of the second powder to deionized water is 1:(4-6), the reactor is set at 200-300 r / min and stirred for 10-20 min, sodium bicarbonate is added to the obtained product to adjust the pH value to 7-8, octenyl succinic anhydride is added into the reactor, and the mass of the octenyl succinic anhydride is 2-4% of the mass of the second powder, the reactor is set to be heated to 40-50° C., the speed is 80-100 r / min, and the mixture is stirred for 4-6 min under heat preservation, the product obtained after the stirring and heat preservation is added into a centrifuge for centrifugal treatment, the centrifuge is set at 4000-5000 r / min for 6-10 min, the supernatant is discarded, a precipitate is obtained, the obtained precipitate is sent into an oven, the oven is set at 42-44° C. for drying for 50-60 min, and then ground, the powder particle size is 6-10 μm, and modified starch is obtained.
8. The mud cake hardening enhancer for drilling fluid according to claim 1, characterized in that: The film-forming agent is polymethyl methacrylate.
9. The mud cake hardening enhancer for drilling fluid according to claim 1, characterized in that: The chelating agent is ethylethylenediaminetriacetic acid, and the asbestos is selected from fibers with a length of 20 to 40 μm and a diameter of 0.4 to 1 μm.
10. A method for preparing the mud cake hardening enhancer for drilling fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weigh bishydroxyethoxypropyl polydimethylsiloxane, film-forming agent, chelating agent and asbestos as needed and add them into a mixer. Set the mixer to 800-1000 r / min and stir for 1-3 hours to obtain a primary mixture; S2: adding a hardener, an additive and modified starch to the primary mixture, setting the mixer at 200-400 r / min for stirring for 6-8 minutes, and preparing a mud cake hardening enhancer for drilling fluid.
Citation Information
Patent Citations
Mud cake hardening enhancer for drilling fluid
CN108587579A
Mud cake toughening improver for drilling fluid and preparation method of mud cake toughening improver
CN109652032A
Leak blocking agent for drilling fluid
CN110373168A
Temperature-resistant and salt-resistant filtrate reducer for drilling fluid, and preparation method thereof
CN110577622A
Environment-friendly temperature-resistant and salt-resistant filtrate loss reducer for well drilling and preparation method thereof
CN110628396A